A review of the systematics, species identification and diagnostics of the Trypanosomatidae using the maxicircle kinetoplast DNA: from past to present. Issue 6 (June 2020) - Kaufer, Alexa; Stark, Damien; Ellis, John
Graphical abstract: Highlights: Advancements in molecular biology have revolutionised the genetic approach to trypanosomatid systematics. The kinetoplast represents a unique taxonomic and diagnostic marker. We propose the use of maxicircle DNA for any future phylogenetic analyses of the Trypanosomatidae. Abstract: The Trypanosomatid family are a diverse and widespread group of protozoan parasites that belong to the higher order class Kinetoplastida. Containing predominantly monoxenous species (i.e. those having only a single host) that are confined to invertebrate hosts, this class is primarily known for its pathogenic dixenous species (i.e. those that have two hosts), serving as the aetiological agents of the important neglected tropical diseases including leishmaniasis, American trypanosomiasis (Chagas disease) and human African trypanosomiasis. Over the past few decades, a multitude of studies have investigated the diversity, classification and evolutionary history of the trypanosomatid family using different approaches and molecular targets. The mitochondrial-like DNA of the trypanosomatid parasites, also known as the kinetoplast, has emerged as a unique taxonomic and diagnostic target for exploring the evolution of this diverse group of parasitic eukaryotes. This review discusses recent advancements and important developments that have made a significant impact in the field of trypanosomatid systematics and diagnostics in recent years.